The place of metals in human life - Sabirova Dilorom Kabulovna; Bobonorov Alimarddon Nurali ugli; Abdusaidov Nodirbek Akmal ugli (Open Academia, 2025)
This article analyzes the use of metals in various aspects of human life and their significance. The wide application of metals in daily life, as well as in industries, transportation, medicine, and technology, highlights the importance of utilizing their valuable properties. The article discusses the use of key metals in construction materials, transportation vehicles, technological devices, as well as in medicine and energy sectors. Environmental issues arising from the use of metals are also addressed. The article emphasizes the importance of efficient and proper use of metals for human life, as well as their environmental impact. Understanding the significance of metals and the necessity of their environmentally correct usage is the main focus of the article
Keywords: Metals; Construction materials